Usulan Manajemen Strategik Pada Rizky Berkah Mebeul - Rizal, Muhammad; Umi, Lita Permata; Hadiantini, Ratih (LPPM UNIBI, 2022)
The furniture industry is one of the fastest-growing sectors in Indonesia, supported by abundant natural resources and the creativity of human resources. SMEs play a vital role in this industry, including Rizky Berkah Meubeul, which focuses on producing and marketing wooden furniture. Despite its potential market, the business faces challenges in product innovation, limited marketing reach, and manual cash flow recording. This study aims to develop product innovation, expand marketing through online media, and establish a more effective financial recording system. The research uses a descriptive analysis method with steps including technology marketing training, product innovation education, and the implementation of a structured financial recording system. The results are expected to enhance Rizky Berkah Meubeul's competitiveness, broaden market reach, and simplify financial management to support sustainable growth.